ZARûRİYYÂT DÜZEYİNDEKİ GÂÎ DEĞERLERİN MAHİYETİ VE EVRENSEL NİTELİĞİ ÜZERİNE - Ali Pekcan (İslami İlimler Dergisi)
Islam has set various rules in order to make human being happy. As setting the rules it observes some purposes and objectives provided that they are absolutely to the benefit of human being and it has not established any non-justified and purposeless rule. If Islamic rules are necessarily studied in view of source and method, it is possibly said that the source means evidences (dalil) which are the bases of the rules and the method means the procedure of deducting these rules from the evidences. To perform ijtihad by observing purposes of the law is a procedure signifying that mujtahid considers basic inherent (natural)necessary (indispebsable) needs and bases rules on them when he deducts the rules from evidences. Thanks to this procedure, not only would the capability and being binding of the source turn out, but the cause and the divine wisdom behind his act also would be understandable for the sane adult (mukallaf).